"Influence of Silica Nanoparticles on Physical and Mechanical Performance of Polyester Matrix Composites " - Hiyam Raheem Sharhan; Ahmed Jadah Farhan (Genius Journals, 2023)
The experimental procedure involved preparing composite materials using unsaturated polyester resin, cement, and silica nanoparticles. The materials were mixed in specific weight ratios and subjected to various tests. Field Emission Scanning Electron Microscope (FE-SEM) analysis showed that the presence and distribution of silica particles within the polymer matrix improved the mechanical properties of the composites.The impact strength of the composites increased after reinforcement with silica particles, indicating improved toughness and resistance to fracture.Hardness testing revealed that the addition of reinforcing materials increased the hardness of the composites compared to the polymer alone Thermal conductivity showed a slight increase with the addition of cement nanoparticles, but decreased when silica nanoparticles were added. Compressive strength and tensile strength tests demonstrated that the reinforced composites had higher strength values compared to the unreinforced polymer.Overall, the experimental results indicated that incorporating silica particles and cement nanoparticles into the unsaturated polyester resin enhanced the mechanical properties of the composites.
Keywords: Unsaturated polyester resin; Cement; silica nanoparticles